Taytay Garments Studios and Community Center - Badar, Denise Anne D.
Today, the Garments Capital has become well known because of its quality and cheap products. As the municipality prepares bidding for cityhood, empty are now being developed. It is only fitting that in these times of redevelopment, that the fundamental elements be looked into once again. The image of Taytay that will be known locally and globally, is what's put in the spotlight once it succeeds in becoming a beautiful city. The agenda seeks to address the issues on the establishment of a clearer image, a participative community while taking advantage of its location and resources. The study focuses on the possible architectural interventions that could help improve the imageability of the city.